Evaluation of reaction parameters of the phenol steam reforming over Ni/Co On ZrO2 using the full factorial experimental design - Nabgan, W. (MDPI AG, 2016)
Full factorial experimental design with 32 runs was used to investigate the significant and interaction variable of the reaction parameters on phenol steam reforming toward hydrogen production. Effects of selected factors on the phenol conversion (Y1) and hydrogen yield (Y2) were evaluated. These factors were as follows: (A) temperature (500 and 800 °C); (B) feed flow rate (0.16-0.46 mL/min); (C) catalyst weight (0.1-0.3 g); (D) Ni-Co ratio (0-1); and (E) phenol concentration in the feed (2-10 wt %). Ni and Co over ZrO2 support for catalytic performance of phenol steam reforming (SRP) was prepared by the impregnation method. The result indicated that all the main independent variables had significant influence on the dependent variable of Y1 and Y2 with a range of 2.7%-96.8% and 21.4%-72.4%, respectively. Additionally, some interaction variables like AE, BE, CE, and DE have also influenced the Y1 and Y2 responses. This design showed that the best initial conditions that produced maximum Y1 and Y2 responses were at 800 °C, 0.16 mL/min feed flow rate, 0.3 g of catalyst, 0 ratio of Ni-Co (Co/ZrO2), and 10 wt % of phenol in the feed, where the phenol conversion was predicted to be 94.98% and the hydrogen yield was predicted to be 67.4%. Within the limits the variables were examined, a regression model which well-fitted the experimental data was proposed. The regression model were reduced to simplify and to get the significant regression coefficient with p-value less than 0.05.